2017
DOI: 10.1038/cddis.2017.481
|View full text |Cite
|
Sign up to set email alerts
|

STAT1β enhances STAT1 function by protecting STAT1α from degradation in esophageal squamous cell carcinoma

Abstract: STAT1, which carries tumor suppressor functions in several models, consists of two isoforms, namely STAT1α and STAT1β. The biological function and significance of STAT1β has never been examined in human cancer. We examined STAT1β function in esophageal squamous cell carcinoma (ESCC) by transfecting a STAT1β gene into various ESCC cell lines. The interaction between STAT1α and STAT1β was examined by using co-immunoprecipitation and confocal microscopy. The prognostic significance of STAT1β expression, detectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…We cannot completely rule out other mechanisms that can result in the STAT1 increase in the AGS cell line by ADAR1 knockdown. For example, a recent study showed that STAT1β can enhance STAT1 function by protecting STAT1α from degradation in esophageal squamous cell carcinoma [ 31 ]. STAT1β, a naturally spliced isoform of STAT1, lacks a 38-amino acid segment that includes the conserved STAT1 S727 phosphorylation site and most of the C-terminal transactivation domain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot completely rule out other mechanisms that can result in the STAT1 increase in the AGS cell line by ADAR1 knockdown. For example, a recent study showed that STAT1β can enhance STAT1 function by protecting STAT1α from degradation in esophageal squamous cell carcinoma [ 31 ]. STAT1β, a naturally spliced isoform of STAT1, lacks a 38-amino acid segment that includes the conserved STAT1 S727 phosphorylation site and most of the C-terminal transactivation domain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 and STAT1 transcriptional activity analyses were performed. Transcription activity was measured by a luciferase reporter gene assay, 12 using the Dual-Luciferase reporter assay system according to the manufacturer’s instructions (Promega Corporation, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear and cytoplasmic protein of ESCC cells was extracted using an NE-PER protein extraction kit (Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer’s instructions as described previously. 12 Oligonucleotide pull-down assays were performed with an annealed nucleotide comprising the STAT3 or STAT1 consensus site with a biotin label.…”
Section: Methodsmentioning
confidence: 99%
“…IHC staining was performed using the EnVision System using peroxidase labeling (Dako, Carpinteria, CA) as described previously [11]. IHC staining was examined by two pathologists who were blinded to the clinical outcome.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Nuclear and cytoplasmic extraction and western blot analysis NE-PER TM nuclear and cytoplasmic extraction reagents (Thermo Scienti c, MA, USA) were used to separate and prepare cytoplasmic and nuclear extracts from ESCC cells. Western blotting was performed as described previously [11]. Antibodies against human β-actin, MAP2K3, p-MAP2K3, EGFR, p-EGFR, STAT1, p-STAT1, STAT3, p-STAT3, caspase 3, cleaved(cl-) caspase 3, GFP, Ki67, Flag, Ub, HA, MDM5, cleaved(cl-) PARP were purchased from Cell Signaling Technology (MA, USA).…”
Section: Introductionmentioning
confidence: 99%